Chapter La reprise du dialogue avec la slavistique occidentale après la mort de Stalin. L'exemple de Julian Grigorevič Oksman (1894/95-1970) - Catherine, Depretto (Biblioteca di Studi Slavistici, 2017)
Prominent historian of Russian literature, one of the best pushkinists of his time, Ju. Oksman was sent to a camp in Kolyma in 1936. Upon his release in 1947, he found a position at Saratov University, then he moved to the Institute of World Literature a decade later. Because of his anti-stalinism, he was fired from his academic positions in 1964 and until the perestroika it was forbidden to write about him in USSR. His letters to Ludwig Domherr or Gleb Struve provide a rich material of the scholar's determination to revive the dialogue with the West and a testimony of his courageous position.